2023
DOI: 10.1021/acs.jpcc.3c00597
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Origin of Enhanced Selectivity through the Halogenation of a Single Mn Atom on Graphitic C3N4 for Electrocatalytic Reduction of CO2 from First-Principles Calculations

Renna Shakir,
Hannu-Pekka Komsa,
A. S. K. Sinha
et al.

Abstract: The electrochemical reduction of CO 2 to valuable products is a critical process that can potentially address energy and environmental challenges. Single-metal atom catalysts have gained significant attention because of their high efficiency and potential to mitigate the challenges associated with traditionalmetal nanocatalysts. In particular, non-precious-metal-based catalysts are of great interest because of their low cost and abundance in the Earth's crust. This work is a comprehensive study to reveal the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Thus, further H adsorption is inhibited, thereby suppressing the HER activity. In the case of MnCl, consistent with prior research, the chlorination leads to the complete half-filling of d-orbitals (Figure e), resulting in enhanced stability . This upward shift was particularly noticeable in all d-orbitals postchlorination, with a prominent change in the down-d z 2 orbital, originally situated at the E F without a Cl atom.…”
Section: Results and Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Thus, further H adsorption is inhibited, thereby suppressing the HER activity. In the case of MnCl, consistent with prior research, the chlorination leads to the complete half-filling of d-orbitals (Figure e), resulting in enhanced stability . This upward shift was particularly noticeable in all d-orbitals postchlorination, with a prominent change in the down-d z 2 orbital, originally situated at the E F without a Cl atom.…”
Section: Results and Discussionsupporting
confidence: 88%
“…In our endeavor to explore the impact of pH on catalyst activity, our earlier study on MnCl@g-C 3 N 4 revealed that secondary selectivity remained independent of pH. However, Varela et al experimentally demonstrated that CO selectivity increased with higher pH on graphene-embedded Fe–N–C motifs, resulting in higher Faradaic efficiency at pH = 6.8 .…”
Section: Results and Discussionmentioning
confidence: 94%
See 3 more Smart Citations